The Bougainvillea mealybug Phenacoccus peruvianus, a rapid invader from South America to Europe - Beltrà, A.; Soto, A.; Germain, J.-F.; Matile-Ferrero, D.; Mazzeo, G.; Pellizzari, G.; Russo, A.; Franco, J.C.; Williams, D.J. (ENTOMOLOGIA HELLENICA, 2010)
Scale insects are frequent invaders of new territories. The Bougainvillea mealybug, Phenacoccus peruvianus Granara de Willink, 2007, was recorded in Europe for the first time in 1999 in Spain (Almeria) and later in 2002 in Italy (Sicily). Initially, this unknown species was identified provisionally as Phenacoccus sp. Records of this species became frequent later when it was found in other localities in Spain (including the Balearic Islands), Great Britain, France (including Corsica), Monaco, and Portugal. The host plants of this mealybug were in most cases species of Bougainvillea.